China\'s CBDC payment infrastructural power and the Global South - Luz, Shelton Ferreira e Silva (2025)
China has established itself as a global leader in the implementation of a Central Bank Digital Currency (CBDC). During the initial decade of implementation (2014-2024), this initiative signified a strategic inflection point in China\'s political and economic relations, wielding extensive international ramifications. This research examines the internationalization of the Chinese CBDC, focusing analytically on its development in the Global South. Proceeding from an exploratory approach, the study investigates the fundamental policies driving China\'s establishment of an international infrastructure based on advanced cross-border payment technologies. The findings indicate that China strategically utilizes infrastructure in the Global South to achieve two primary objectives: (i) promote the internationalization of its digital currency through the establishment of an autonomous digital platform, and (ii) establish a sufficient network to circumvent the monetary dominance of the Global North, which controls international payment systems such as SWIFT (Society for Worldwide Interbank Financial Telecommunication), often leveraging these systems as instruments of coercion. Consequently, the primary contribution of this research has been to demonstrate how the Global South occupies a strategic role in China\'s foreign and economic policies by integrating initiatives to build infrastructural digital monetary platforms. Collectively, these initiatives aspire to augment financial interconnectedness, curtail asymmetries, and diminish reliance on the coercive authority historically wielded by the Global North within the international payments system.